Capriccio a conversation piece for music in one act - Strauss, Richard, 1864-1949; Krauss, Clemens, 1893-1954; Fleming, Renée; Henschel, Dietrich, 1967-; Otter, Anne Sofie von; Hawlata, Franz; Trost, Rainer; Finley, Gerald, 1960-; Tear, Robert; Roussillon, François; Schirmer, Ulf, 1959-; Carsen, Robert; et al. (TDK, 2005)
Two rival suitors, one a poet, the other a composer, vie for the love of a beautiful woman who must decide which one she loves.